Australian directions in indigenous education 2005-2008 - Ministerial Council on Education, Employment, Training and Youth Affairs (Australia) (Canberra : Ministerial Council on Education, Employment, Training and Youth Affairs, 2006)
The report catalogues achievments made in the area of indigenous education and notes the areas that still need attention. It gives recommendations and timeframes for when these should be achieved.
Title from title page (viewed on 23 Aug. 2006)
Bibliography: p. 15-16.
Text.
Mode of access: Internet via World Wide Web. Available at: http://www.mceetya.edu.au/verve/_resources/Australian_Directions_in_Indigenous_Education_2005-2008.pdf
System requirements: Adobe Acrobat for viewing pdf files.
Selected for archiving
Keywords: Aboriginal Australians -- Education; Aboriginal Australians -- Social conditions